Ionically dispersed Fe(ii)–N and Zn(ii)–N in porous carbon for acidic oxygen reduction reactions. Issue 83 (5th October 2017) - Liang, Sihui; Chen, Renjie; Yu, Peiwen; Ni, Mei; Zhang, Qiao; Zhang, Xiaoling; Yang, Wen
Abstract : A bimetallic Fe, Zn/N/C catalyst with high metal loading, demonstrating high activity for ORR processes in acidic electrolytes. Abstract : Inspired by the zinc protoporphyrin found in red blood cells during heme production, we have developed a novel type of bimetallic Fe, Zn/N/C catalyst with high metal loading (Fe 1.2 wt% and Zn 1.7 wt%), demonstrating high activity and high stability for oxygen reduction processes in acidic electrolytes.